2001
DOI: 10.1128/jvi.75.15.6786-6799.2001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding by Kaposi's Sarcoma-Associated Herpesvirus Lytic Switch Protein Is Necessary for Transcriptional Activation of Two Viral Delayed Early Promoters

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV; also known as human herpesvirus-8) establishes latent and lytic infections in both lymphoid and endothelial cells and has been associated with diseases of both cell types. The KSHV open reading frame 50 (ORF50) protein is a transcriptional activator that plays a central role in the reactivation of lytic viral replication from latency. Here we identify and characterize a DNA binding site for the ORF50 protein that is shared by the promoters of two delayed early gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
264
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(270 citation statements)
references
References 34 publications
(43 reference statements)
3
264
3
Order By: Relevance
“…Removal of all four sequences had little effect on RTA-activated expression from the ORF57 promoter; however, a 40 bp region between nt 81904 and 81944 was found to be essential for RTA responsiveness. A significant 16 bp homology between the ORF57 region and the 5 0 sequences preceding the HHV-8 K8, basic leucine zipper (bZip) gene were reported (Wang et al, 2001a); moreover, a near-identical 25 bp sequence was subsequently described by Lukac et al (Lukac et al, 2001). Mutational analyses revealed that both the K8 and ORF57 sequences were responsive to RTA and conferred RTA responsiveness to heterologous promoters.…”
Section: Rta Interacts With Various Promoters and Factors To Mediate mentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of all four sequences had little effect on RTA-activated expression from the ORF57 promoter; however, a 40 bp region between nt 81904 and 81944 was found to be essential for RTA responsiveness. A significant 16 bp homology between the ORF57 region and the 5 0 sequences preceding the HHV-8 K8, basic leucine zipper (bZip) gene were reported (Wang et al, 2001a); moreover, a near-identical 25 bp sequence was subsequently described by Lukac et al (Lukac et al, 2001). Mutational analyses revealed that both the K8 and ORF57 sequences were responsive to RTA and conferred RTA responsiveness to heterologous promoters.…”
Section: Rta Interacts With Various Promoters and Factors To Mediate mentioning
confidence: 99%
“…However, RTA does not recognize the same sequence element in all responsive promoters. This diversity of recognition suggests that on some promoters, other viral and host factors may direct or augment DNA binding and may influence the diversity of RTA transactivation (Seaman et al, 1999;Lukac et al, 2001;Sakakibara et al, 2001;Wang et al, 2001a;Chang et al, 2002;Deng et al, 2002b;Saveliev et al, 2002).…”
Section: Rta Interacts With Various Promoters and Factors To Mediate mentioning
confidence: 99%
“…Figure 3A schematically depicts the organization of the relevant portions of the MTA and SSB promoters, indicating the location of the predicted RBP-J recognition element within each. In the MTA promoter, our earlier work (Lukac et al 2001) established that deletion to −106 preserves RTA-inducibility, while deletion to −54 abolishes it, thereby defining a 52-bp sequence that confers RTA responsiveness. The RBP-J site falls within this region, in the antisense orientation relative to the MTA ORF.…”
Section: Rta/rbp-j Interactions In Authentic Viral Promotersmentioning
confidence: 99%
“…Radioactive probes were diluted in water to a final concentration of 105 cpm/µL. DNA binding reactions were performed in a manner similar to that described (Lukac et al 2001). Briefly, proteins from RRL were mixed with 1 µg poly (dI-dC) (Sigma) in 1× DNA binding buffer for 30 min on ice.…”
Section: Electromobility Shift Assays (Emsa)mentioning
confidence: 99%
See 1 more Smart Citation